Explicating problematic social network sites use: A review of concepts, theoretical frameworks, and future directions for communication theorizing - Lee, Edmund Wei Jian (2017)
The prevalence of social network sites (SNSs) has sparked a growing interest in understanding the development of problematic SNSs use among adolescents. Yet, this nascent area of research is marked by some deficiencies in existing theoretical paradigms. This article seeks to review the state of research in problematic SNSs use—broadly with a specific focus on adolescents—and identify key areas of research for future scholarly work. First, we summarize the historical and recent developments of media addiction and problematic SNSs use research. Second, we discuss the theoretical perspectives that contribute to our understanding of the problematic SNSs use phenomenon and identify the weaknesses of these frameworks. Third, we propose that communication scholars should strive for theoretical integration and examine the impact of microsystem (e.g. parents and peers) and macrosystem (e.g. surveillance culture) on the development of problematic SNSs among adolescents. Directions for future theoretical and methodological approaches are suggested.